Determination of the brittleness of glass fibers on selected mechanical and rheological properties of the polymer composite - Stanislav Miščík; Jozef Dobránsky; Miroslav Gombár; Robert Čep (eXPRESS Polymer Letters)
The paper deals with the influence of the brittleness of glass fibers on the selected performance properties of the fibrous polymer composite. Understanding the fatigue behavior of fiber-reinforced plastics is desirable for exploiting their features in safe, durable, and reliable industrial components. Based on the proposed methodology, it is possible to assess the impact of material reuse on selected mechanical and rheological properties. To verify the methodology by experimental analysis, homopolymer PP reinforced with chemically grafted glass fiber (30 wt%) was selected. The proposed methodology was subsequently verified by experimental analysis and evaluated statistically. The morphology of the fracture surfaces was evaluated, and the fiber-polymer matrix adhesion was monitored at the interface of the fracture surfaces. Based on the measured and evaluated values and fracture surfaces, we can say that the brittleness of the fibers significantly affects the performance properties of the tested polymer composite.